Upfront Treatment of Pediatric High-Risk Neuroblastoma With Chemotherapy, Surgery, and Radiotherapy Combination: The CCCG-NB-2014 Protocol - Zhang, Dongdong; Kaweme, Natasha Mupeta; Duan, Peng; Dong, Youhong; Yuan, Xiaojun (Frontiers in Oncology, 2021)
Purpose: To formulate the optimal treatment strategies for high-risk neuroblastoma, the China Children Cancer Group developed the CCCG-NB-2014 study. The safety and efficacy of this protocol was evaluated. Method: Patients were newly diagnosed with neuroblastoma and defined as high-risk according Children’s Oncology Group study were included. Patients were treated with chemotherapy, surgery and radiotherapy combination. The treatment-related toxicities, response rate, 3-year progression-free survival (PFS) and overall survival (OS) were analyzed. Results: Of 159 patients between 2014 and 2018, 80 eligible patients were enrolled, including 19 females and 61 males, median age was 3.9 years (range 0.9 to 11). After a median follow-up of 24 months (range 3-40), the median overall survival was 31.8 months, 3-years OS was 83.8%. In multivariate analyses, overall survival was affected by N-MYC amplification (hazard ratio 0.212, 95% CI 0.049-0.910; p=0·037) and giant tumor mass (hazard ratio 0.197, 95% CI 0.071-0.552; p=0·002). Median 3-year PFS was 25.8 months, 3-year PFS was 57.5%. On univariate analysis, only giant tumor mass were associated with outcome. 13 deaths were reported, 11 died from the rapid progression of disease and 2 of which were attributed to treatment-related toxicities. The most common adverse reaction was chemotherapy-induced hematological toxicity. Conclusion: The PFS and OS reported in our study were similar to western countries. The CCCG-NB-2014 protocol proved to an efficient regimen with tolerable side-effect for the treatment of pediatric high-risk neuroblastoma.